2020
DOI: 10.3390/v12020156
|View full text |Cite
|
Sign up to set email alerts
|

Imported Human West Nile Virus Lineage 2 Infection in Spain: Neurological and Gastrointestinal Complications

Abstract: We report the first human case of West Nile virus (WNV) lineage 2 infection imported to Spain by a traveler returning from Romania. Serum, cerebrospinal fluid and urine samples were analyzed and West Nile virus infection was identified by PCR and serological tests. The patient developed fever, diarrhea and neurological symptoms, accompanied by mild pancreatitis, described previously in very few cases as a complication of WNV infection and by alithiasic cholecystitis. Viral RNA was detected in urine until 30 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Lineage 2, also neurotropic but with lesser virulence, comprises isolates from Sub-Saharan Africa, Madagascar, and Europe. Viruses in this lineage have caused several outbreaks in humans, horses, and birds [76,146,150,[156][157][158][159][160].…”
Section: Genetic Diversification Within the Wnv Speciesmentioning
confidence: 99%
“…Lineage 2, also neurotropic but with lesser virulence, comprises isolates from Sub-Saharan Africa, Madagascar, and Europe. Viruses in this lineage have caused several outbreaks in humans, horses, and birds [76,146,150,[156][157][158][159][160].…”
Section: Genetic Diversification Within the Wnv Speciesmentioning
confidence: 99%
“…The wide variety of circulating West Nile virus strains results in varying degrees of infection severity. For example, studies have shown that the T249P substitution in the NS3 protein leads to increased virulence [13][14][15][16]. Another important factor determining pathogenicity is the glycosylation of the envelope protein E [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Less than 1% of infected cases develop a neuroinvasive disease (WNND) such as encephalitis, meningitis, and acute flaccid paralysis, frequently associated with risk factors such as aging, solid organ transplant, diabetes, hypertension, and other immunosuppression conditions related to fatal outcome ( Lindsey et al., 2012 ). Moreover, atypical or rare presentations of WNV disease (WNVD) such us myocarditis, pancreatitis, hepatitis, cerebellitis, rhabdomyolysis, and ocular manifestations have also been described ( Hasbun et al., 2016 ; Konjevoda et al., 2019 ; Velasco et al., 2020 ). WNVD has sometimes been associated with several sequelae, the most frequent being muscle weakness, fatigue, myalgia, memory loss, depression, and difficulty doing activities of daily living ( Carson et al., 2006 ; Hughes et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%